The Hypothesized Effects of Ability in the Turnover Process - Jackofsky, Ellen F.; Peters, Lawrence H. (Academy of Management Review, 1983)
Findings from studies that have investigated the relationship between task-relevant ability and turnover have been inconsistent. A process model is presented that suggests that ability may be related to turnover through the individual's perception of both the ease and desirability of movement. The potential effect of ability on the turnover process and its practical and theoretical implications are discussed.